Aerobic treatment of black ripe olive processing streams to reduce biological contamination. (December 2020) - García-Serrano, Pedro; Romero, Concepción; de Castro, Antonio; García-García, Pedro; Montaño, Alfredo; Medina, Eduardo; Brenes, Manuel
Abstract: A new aeration treatment of black ripe olive streams prior to their vacuum evaporation was studied. It was found that the aeration for two days of these solutions reduced the chemical oxygen demand (COD) of the distillate phase (>80%) generated during their vacuum evaporation; although the temperature (14–38 °C) and the air flow rate (10–50 L air/h/L) had a great influence on this reduction. Moreover, the COD in the distillate was mainly associated with the presence of acetic acid (~400 mg/L) and ethanol (~500 mg/L), the later substance being eliminated by strong aeration. Additionally, the growth of native aerobic microorganisms, mainly Acetobacter, increased the pH of the wastewater to 7–8 units, thus avoiding evaporation of the acetic acid salt formed. These results make the use of the distillate for plant irrigation viable and its discharge into municipal depuration plants possible, given the low COD (<500 mg/L) reached with this new method. Industrial relevance: The worldwide production of table olives is annually increasing but the management of the solutions generated during olive processing is limiting this expansion, in particular due to their high salt content. Factories are nowadays concentrating these solutions by using vacuum evaporation but the contamination of the distillate is too high. The present work has been carried out based on industry demand for low cost and easy handle technology able to reduce COD in distillates. The results of the present study showed that the content in ethanol and acetic acid of distillates can be reduced to a large extend by simple aerating of the solutions prior to the vacuum evaporation step, and this open the possibility of their reuse for plant irrigation. Highlights: An aeration pre-treatment of table olive waste streams reduced the COD in distillates (>80%). Ethanol (1100–1400 mg/L) can be eliminated from olive streams by aeration. Growth of native microorganisms increased the pH and it prevented evaporation of acetic acid salt. Flow rate higher than 25 L air/h/L is needed for aerobic pre-treatment.